Perbanyakan In Vitro Sansevieria trifasciata ‘Lorentii’: Regenerasi Tunas, Pengakaran, dan Aklimatisasi Planlet - Yusnita, ,; Wahyuningsih, Triani; Sulistiana, Puji; Hapsoro, Dwi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
This research aimed to study effects of benzyladenine (BA) on in vitro shoot formation and effects of indolebutyric acid(IBA) and acclimatization media on ex vitro rooting and acclimatization of Sansevieria trifasciata ‘Lorentii’. Leaf segmentswere taken from young fully-expanded leaves, surface sterilized and cultured on Murashige and Skoog (MS) basal mediumcontaining 0.25 mg L-1 2,4-dichlorophenoxyacetic acid (2,4-D) for 2 weeks, transferred to medium without growth regulatorfor 2 weeks, and then subcultured on MS medium containing BA (0, 0.5, 1 and 2 and 5 mg L-1). The results showed thatadventitious shoot regeneration occured after callus formation. The best BA concentration was 2 mg L-1, producing 4.5 shootsper explants in 3 months and 11.1 shoots per explant in 4 months. Application of 2000 ppm IBA and the use of acclimatization medium consisting rice husk charcoal and compost (1:1) produced the highest number of primary roots, length of roots and root fresh weight. However, the ex vitro rooting did not influence the success of plantlet acclimatization, the survival rate being 96% and there were no significant difference in plant growth.Keywords: benzyladenine, ex vitro, indolebutyric acid, 2,4-dichlorophenoxyacetic acid, micropropagation, Sansevieriatrifasciata